2015
DOI: 10.1080/2162402x.2014.1002721
|View full text |Cite|
|
Sign up to set email alerts
|

IL-15 suppresses colitis-associated colon carcinogenesis by inducing antitumor immunity

Abstract: IL-15 regulates the development, survival, and proliferation of multiple innate and adaptive immune cells and plays a dual role, inducing both tumor cell growth and antitumor immunity. However, the role of IL-15 in inflammation-induced cancer remains unclear. To explore this, we have compared the colon carcinoma burden of Il15 ¡/¡ and Il15ra ¡/¡ mice with wild type (WT) mice after induction of colitis-associated colon carcinogenesis utilizing the AOM/DSS model. Compared to WT mice, Il15¡/¡ but not Il15ra ¡/¡ m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 62 publications
1
19
0
Order By: Relevance
“…This conclusion is in line with literature reporting prevention of lung or breast cancer metastasis being dependent on mature KLRG1 + NK cell numbers 27 32 and IFNγ-mediated mechanisms 33 . Furthermore, our findings on the role of IL15-driven NK cell-mediated inhibition of tumor growth are in accordance with our previous report using the DSS/AOM model of colitis-associated colon carcinogenesis 34 and the findings that IL15 induces very densely granulated NK cells that can eliminate large established solid tumors in the absence of T and B cells 35 . In this latter model expression of the IL15Rα on cancer cells was needed to efficiently induce granulated NK cells, and expression on host stromal cells was essential to prevent tumor relapse.…”
Section: Discussionsupporting
confidence: 93%
“…This conclusion is in line with literature reporting prevention of lung or breast cancer metastasis being dependent on mature KLRG1 + NK cell numbers 27 32 and IFNγ-mediated mechanisms 33 . Furthermore, our findings on the role of IL15-driven NK cell-mediated inhibition of tumor growth are in accordance with our previous report using the DSS/AOM model of colitis-associated colon carcinogenesis 34 and the findings that IL15 induces very densely granulated NK cells that can eliminate large established solid tumors in the absence of T and B cells 35 . In this latter model expression of the IL15Rα on cancer cells was needed to efficiently induce granulated NK cells, and expression on host stromal cells was essential to prevent tumor relapse.…”
Section: Discussionsupporting
confidence: 93%
“…Colorectal cancer patients with genomic deletion of IL15 have a significantly higher risk of tumor recurrence and show reduced survival compared with patients with intact IL15 ( 19 ). Moreover, IL-15 is expressed in human CRC cells in situ ( 120 ).…”
Section: Interleukin-15mentioning
confidence: 99%
“…In fact, IL-10 KO mice are highly susceptible to UC and CAC due to uncontrolled inflammation in the colon (139, 140). IL-15 suppresses CAC by promoting anti-tumor immunity by CD8 + T cells and NK cells (141). Several studies have shown that either inhibition of a combination of proinflammatory cytokines, cytokine receptors or addition of recombinant anti-inflammatory cytokines will likely reduce the CAC in IBD patients.…”
Section: Signaling Molecules As Therapeutic Targetsmentioning
confidence: 99%